2015
DOI: 10.3390/ijerph121214994
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerable Populations Perceive Their Health as at Risk from Climate Change

Abstract: Climate change is already taking a toll on human health, a toll that is likely to increase in coming decades. The relationship between risk perceptions and vulnerability to climate change’s health threats has received little attention, even though an understanding of the dynamics of adaptation among particularly susceptible populations is becoming increasingly important. We demonstrate that some people whose health will suffer the greatest harms from climate change—due to social vulnerability, health susceptib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
57
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 51 publications
7
57
1
2
Order By: Relevance
“…While some research has indicated that low-income individuals are disengaged from the problem of climate change [30], our results suggest that having a lower household income significantly predicts one's perception of climate change as a health threat, reflecting an accurate perception of having fewer resources to adapt. These results echo findings in Maryland residents, where vulnerable populations (including those in low-income households) perceived their own climate change health vulnerability to be greater than the public at large [31]. Discrepancies between national and local surveys highlight the regional variation in climate change risk perception, which may be due to personal experience with extreme weather [17] among other factors, and underscores the importance of continued local research and preparedness efforts.…”
Section: Perceptions Of Heat and Climate Change Risksupporting
confidence: 56%
“…While some research has indicated that low-income individuals are disengaged from the problem of climate change [30], our results suggest that having a lower household income significantly predicts one's perception of climate change as a health threat, reflecting an accurate perception of having fewer resources to adapt. These results echo findings in Maryland residents, where vulnerable populations (including those in low-income households) perceived their own climate change health vulnerability to be greater than the public at large [31]. Discrepancies between national and local surveys highlight the regional variation in climate change risk perception, which may be due to personal experience with extreme weather [17] among other factors, and underscores the importance of continued local research and preparedness efforts.…”
Section: Perceptions Of Heat and Climate Change Risksupporting
confidence: 56%
“…Epidemiologic research has shown that certain populations are more vulnerable to the negative effects of global warming, including people with preexisting medical conditions (U.S. Global Change Research Program, ), and that these vulnerable groups are more likely to feel like they are already at risk from global warming (Akerlof et al, ). Additionally, attitudes toward global warming are highly polarized in terms of political ideology, with liberals being more concerned and supportive of action to address global warming relative to conservatives (Dunlap et al, ; McCright & Dunlap, ).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, insurance coverage increases survival chances in the event of an extreme climate event (Lang et al, 2016), while a lack of insurance exacerbates the declining availability of medical services for low‐income households. This situation is a serious problem for most low‐income households or near‐low‐income households in the U.S. (Akerlof, Delamater, Boules, Upperman, & Mitchell, 2015). Economic disparity makes vulnerable populations, especially the socially disadvantaged, more susceptible to public health problems during climate change (Brown, Spickett, & Katscherian, 2014; Pelkowski & Berger, 2003).…”
Section: Healthcare Reformmentioning
confidence: 99%